Plaque, Dr. Bhau Daji Lad Musuem - Ghosh, Ayan (2023)
Victoria and Albert Museum opened on 2 May 1872 and was named in honor of Queen Victoria (1819–1901) and her consort, Prince Albert (1819–61). In 1975, the museum was renamed in honor of Dr. Bhau Daji Lad (1824-74), a Sanskrit scholar and polymath, who was the first Indian sheriff of Mumbai and played a key role in the establishment of the museum.